Novel mastadenovirus infection and clinical disease in a pygmy marmoset (Callithrix [Cebuella] pygmaea) - Gál, János; Hornyák, Ákos; Mándoki, Míra; Bakonyi, Tamás; Balka, Gyula; Szeredi, Levente; Marosán, Miklós; Ludányi, Tibor; Forgách, Petra; Sós, Endre; Demeter, Zoltán; Farkas, Szilvia L. (Veterinary microbiology, 2013)
We describe the detection and successful isolation of a novel mastadenovirus from a pygmy marmoset (Callithrix [Cebuella] pygmaea) that died following an episode of severe respiratory signs. Pathologic/histopathologic examination revealed hydrothorax and catarrhal bronchopneumonia with pronounced desquamation of the bronchiolar epithelial cells, while in other airways a marked hyperplasia of the epithelial lining and numerous giant cells could be observed. We obtained partial sequence data from the adenoviral DNA-dependent DNA-polymerase gene of the isolated strain and analyses of this region showed the highest level of identity to the recently described bat adenoviruses (strains PPV1 and TJM) and the type 2 canine adenovirus. Similar results were gained by phylogenetic calculations indicating that this novel marmoset adenovirus is only distantly related to reference Old and New World primate adenoviruses and formed a monophyletic group with bat and canine adenoviruses and the equine adenovirus 1. Even though the source of the infection remained unknown, our results could imply the possibility of a cross-species transmission of the virus from an anonymous host to the pygmy marmoset.